The structure of the intact ribosome and ribosomal subunit interactions - Cate, Jamie H. Doudna (Henry Stewart Talks, 2008)
Introduction to the architecture of the bacterial ribosome, Ribosome composition and landmarks, Ribosomal subunit interface, Conformational changes in the ribosome
Archived at 2020/08/13